Pengaruh Suhu Dan Lama Pengeringan Terhadap Sifat Kimia Dan Organoleptik Sale Pisang Kapas (Musa Comiculata) - Marwati Marwati; Yuliani Yuliani; Yulian Andriyani; Mentari Mentari (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2017)
Banana “kapas” is an original banana cultivar from Samarinda, with the characteristics at the time of mature is yellow fruit skin color, flesh color yellowish white and has a sweet taste. During this time the banana kapas has not been utilized properly. Based on the characteristics possessed by banana kapas can be processed into the processed products sale banana. This study aims to determine the effect of temperature and drying time on the chemical properties of sale of banana kapas produced, the level of panelist reception at organoleptic test and to get the time and temperature of the dryer that produces a quality banana sale based on chemical properties and organoleptic. The results showed that the temperature and duration of the dryer and its interactions had the significant effect on water content, ash content, vitamin C and reducing sugar content. Treatment with temperature 75oC and 21 hours drying time gave the best result with water content, ash content, vitamin C and reducing sugar are 32.80%, 1.13%, 60.65 mg/g and 16.08% respectively. For hedonic test, hedonic values of color, flavor, aroma and texture is like the hedonic quality of brown, sweet taste, rather banana flavored and hard texture.